Trajectories for Sustainable Development Goals : Framework and Country Applications - Gable, Susanna (World Bank, Washington, DC, 2015)
Individual countries face the challenge of implementing strategies that help realize the ambitions of the global Sustainable Development Goals (SDG) agenda, adopted by the UN General Assembly in September, 2015. This book presents the Country Development Diagnostics Post-2015 framework and a brief applications of the framework to ten countries.